Protective effect of trans-δ-viniferin against high glucose-induced oxidative stress in human umbilical vein endothelial cells through the SIRT1 pathway. (2nd January 2016) - Zhao, Huijun; Ma, Ting; Fan, Boyi; Yang, Lei; Han, Chao; Luo, Jianguang; Kong, Lingyi
ABSTRACT: Oxidative stress plays a critical role in the pathogenesis of diabetic vascular complications. Trans- δ -viniferin (TVN), a polyphenolic compound, has recently attracted much attention as an antioxidant exhibiting a hypoglycemic potential. In the present study, we aimed at investigating the protective effect of TVN against high glucose-induced oxidative stress in human umbilical vein endothelial cells (HUVECs) and the potential mechanism involved. We found that TVN attenuated reactive oxygen species (ROS) production, increased catalase (CAT) activity and decreased malondialdehyde (MDA) levels to ameliorate cell survival induced by 35 mM glucose. Meanwhile, it inhibited high glucose-induced apoptosis by maintaining Ca 2+ and preserving mitochondrial membrane potential (MMP) levels. The immunoblot analysis indicated that TVN efficiently regulated the cleavage of caspase family, p53, Bax and Bcl-2, all mediated by SIRT1. Furthermore, the increased level of SIRT1 induced by TVN was inhibited by nicotinamide and siRNA-medicated SIRT1 silencing (si-SIRT1), thereby confirming the significant role of SIRT1 in these events. In conclusion, our results indicated that TVN efficiently reduced oxidative stress and maintained mitochondrial function related with activating SIRT1 in high glucose-treated HUVECs. It suggested that TVN is pharmacologically promising for treating diabetic cardiovascular complications.